The Influence of Personal Training Methods on Under Passing Skills In Volleyball Extracurricular Students of State 5 State Junior High School Pangkalpinang (Universitas Negeri Semarang, 2022)
This research was motivated by the students' skills in volleyball extracurricular activities, namely the lack of forearm pass due to lack of mastery of excellent and correct forearm pass techniques. This study aims to determine the effect of individual training methods on volleyball forearm pass skills in extracurricular students of SMP Negeri 5 Pangkalpinang.This research was quantitative research that was a pre-experimental one-group pretest-posttest design. The sample in this study was extracurricular volleyball students at SMP Negeri 5 Pangkalpinang, totaling 22 people with a sampling technique using saturated samples. The data analysis technique in this study used the t-test.Based on the calculation of the hypothesis using the t-test, the results were obtained (t-count = 10.168 t table = 1.721) with a significant level of 0.05, which means Ho was rejected and Ha was accepted. So it could be concluded that individual training methods were affected the volleyball forearm pass skills in extracurricular students at SMP Negeri 5 Pangkalpinang.